Safety, tolerability, and anti-tumor activity of olmutinib in non-small cell lung cancer with T790M mutation: A single arm, open label, phase 1/2 trial. (September 2019) - Kim, Dong-Wan; Lee, Dae Ho; Han, Ji-Youn; Lee, Jongseok; Cho, Byoung Chul; Kang, Jin Hyoung; Lee, Ki Hyeong; Cho, Eun Kyung; Kim, Jin-Soo; Min, Young Joo; Cho, Jae Yong; An, Ho Jung; et al.
Highlights: Olmutinib showed effective clinical activity. The safety profile of olmutinib was manageable. Olmutinib showed potential in T790M-positive NSCLC after failing ≥1 prior EGFR-TKI. Abstract: Objectives: The aim of this phase 1/2 study was to evaluate the safety, tolerability, pharmacokinetics and antitumor activity of olmutinib in patients with epidermal growth factor receptor (EGFR)-mutated non-small cell lung cancer (NSCLC) who had failed ≥ 1 previous line of EGFR-tyrosine kinase inhibitor (TKI) therapy. Materials and methods: Phase 1 consisted of dose-escalation and four dose-expansion parts (1: olmutinib 300 mg once daily; 2A: 800 mg once daily [ EGFR T790 M mutation-positive patients]; 2B: 500 mg twice daily [ EGFR T790 M mutation-positive]; 3: 800 mg once daily [ EGFR T790 M mutation-negative]). In phase 2, EGFR T790 M mutation-positive patients received olmutinib 800 mg once daily. Data from expansion part 2A and phase 2 were integrated (`pooled phase 2′). Each olmutinib cycle was 21 days. Outcomes included: tumor response, treatment-emergent adverse events (TEAEs), pharmacokinetic parameters. Results: Overall, 272 patients received at least one olmutinib dose: dose-escalation (n = 66), expansion parts (n = 165), phase 2 (n = 41). In pooled phase 2, the overall objective response rate, confirmed by independent review, was 55.1% (38/69 evaluable patients; 95% CI, 42.6–67.1). All responses were partial responses; 23 patients had stable disease. Estimated median progression-free survival was 6.9 (95% CI, 5.6–9.7) months; estimated median overall survival was not reached. The most frequent treatment-related AEs were diarrhea (59.2% of patients), pruritus (42.1%), rash (40.8%), and nausea (39.5%). Conclusion: Olmutinib showed effective clinical activity with a manageable safety profile, indicating therapeutic potential for T790M-positive NSCLC patients who have failed ≥ 1 previous line of EGFR-TKI therapy.